Solve for x.
6 – 2x – x = 18

6 – 2x – x = 18 -3x = 18 -6 -3x = 12 x= -4

Question

Asked 1/8/2014 11:44:09 AM

Updated 1/8/2014 1:45:22 PM

1 Answer/Comment

Rating

3

6 – 2x – x = 18

-3x = 18 -6

-3x = 12

x= -4

-3x = 18 -6

-3x = 12

x= -4

Added 1/8/2014 1:45:22 PM

This answer has been confirmed as correct and helpful.

Which best summarizes the lesson Baker learns in "No Gumption"?
A.
Mothers often help their children succeed.
B.
Writers lead easier lives than salespeople.
C.
The seeds of success may be found even in a failure.
D.
Only outgoing people can do well in business.

Question

Not Answered

Updated 40 days ago|11/6/2018 11:30:54 AM

1 Answer/Comment

Evaluate the expression by using the given values of the variables.
y ÷ 4 • 3 – 6 ÷ x + 8 where x = 3 and y = 24

Question

Not Answered

Updated 1/8/2014 1:05:03 PM

1 Answer/Comment

y ÷ 4 • 3 – 6 ÷ x + 8, where x = 3 and y = 24

24 ÷ 4 • 3 – 6 ÷ 3 + 8

6 • 3 - 2 + 8

18 - 2 + 8

18 + 6

= 24

24 ÷ 4 • 3 – 6 ÷ 3 + 8

6 • 3 - 2 + 8

18 - 2 + 8

18 + 6

= 24

Added 1/8/2014 1:05:03 PM

This answer has been confirmed as correct and helpful.

Solve.
2x + 6 –4 **Weegy:** 3(2x + 1) = 3 6x + 3 = 3 6x = 3 - 3 6x = 0 x = 0 **User:** What is the solution to the equation?
5x + 10 = –4x – 17 (More)

Question

Not Answered

Updated 1/8/2014 11:39:04 PM

3 Answers/Comments

2x + 6 –4

= 2x - 2

= 2x - 2

Added 1/8/2014 1:41:28 PM

This answer has been flagged as incorrect.

Flagged by yeswey [1/8/2014 11:38:41 PM]

5x + 10 = –4x – 17

5x + 4x = -17 - 10

9x = -27

x = -3

5x + 4x = -17 - 10

9x = -27

x = -3

Added 1/8/2014 1:43:11 PM

This answer has been confirmed as correct and helpful.

Evaluate the expression by using the given value of the variables.
y ÷ 2 • 4 – 10 ÷ x + 6 where x = 5 and y = 16

Question

Not Answered

Updated 1/8/2014 12:58:26 PM

1 Answer/Comment

y ÷ 2 • 4 – 10 ÷ x + 6 where x = 5 and y = 16

16 ÷ 2 • 4 – 10 ÷ 5 + 6

8 • 4 - 10 ÷ 5 + 6

32 - 2 + 6

30 + 6

= 36

16 ÷ 2 • 4 – 10 ÷ 5 + 6

8 • 4 - 10 ÷ 5 + 6

32 - 2 + 6

30 + 6

= 36

Added 1/8/2014 12:58:26 PM

This answer has been confirmed as correct and helpful.

Solve for x.
12 – 3x – x = 8
A.
–10
B.
–5
C.
1
D.
2 **Weegy:** 3x + 4 = x + 12 3x - x = 12 - 4 2x = 8 x = 4 (More)

Question

Expert Answered

Updated 1/8/2014 1:40:19 PM

1 Answer/Comment

12 – 3x – x = 8

-3x - x = 8 - 12

-4x = -4

x = 1

-3x - x = 8 - 12

-4x = -4

x = 1

Added 1/8/2014 1:40:19 PM

This answer has been confirmed as correct and helpful.

27,940,039

questions answered

There are no comments.